Pendefinisian Semula Konsep Hutang Produktif Ke Arah Gaya Hidup Halal - Ahmad Azrin, Adnan; Mohamad Izzuddin, Abdul Aziz (2017)
The implementation of Musyarakat Mutanaqisat financing contract in Malaysia is still inadequate compared to other countries such as those in the Middle East. In Malaysia, there are 10 Islamic local banks comprise of Affin Islamic Bank Berhad, Maybank Islamic Berhad, CIMB Islamic Bank Berhad, Hong Leong Islamic Bank Berhad, RHB Islamic Bank Berhad and others. However, this article only focuses on two local banks (Affin Islamic Bank Berhad & RHB Islamic Bank Berhad) which offer the Musyarakat Mutanaqisat home financing contract. The implementation of Musyarakat Mutanaqisat home financing contract is less favoured by local banks in Malaysia because it brings higher risk compared to other home financing contracts (Mahmood Muhammad, 2014). The high risk has to be borne by the banks especially due to the sharing element in Musyarakat Mutanaqisat home financing contract (Rulindo, 2009). Is this statement true? If so, what are the actions that banks need to take in order to control these risks? This article aims to identify, analyse, and summarise the risk management in the implementation of Musyarakat Mutanaqisat home financing contract in local banks in Malaysia. A total of four informants comprising two selected Islamic banking officers from Affin Islamic Bank Berhad and RHB Islamic Bank Berhad as well as two academic experts in the field of Islamic banking are involved in the discussion of the implementation of risk management in the Musyarakat Mutanaqisat home financing contract. Semi-structured interviews are conducted on the informants by using purposive sampling method. The findings of this article comprise of discussions on the types of risks inherent in the Musyarakat Mutanaqisat home financing contract. The risks consist of credit risk, liquidity risk, Syariah risk, operational risk and investment equity risk. The risk management of the Musyarakat Mutanaqisat home financing contract by Islamic banking institutions includes three stages namely the early stage of the agreement, the current stage of the agreement and the final stage of the agreement